Risks factors for diarrhea among travellers visiting Bali - Ni Wayan Mega Sri Wahyuni; I Made Ady Wirawan; Made Agus Hendrayana (Universitas Udayana, 2019)
Background and purpose: The number of foreign travellers visiting Bali continues to increase and diarrhea often occur among them. The purpose of this study is to determine the risk factors for the incidence of diarrhea in foreign travellers. Methods: A case-control study was conducted in foreign travellers visiting the international clinic at the Port Health Office at Ngurah Rai International Airport in Denpasar during the period from May to October 2018. Cases were foreign travellers visiting the clinic with diarrhea symptoms. Controls were non-diarrhea foreign travellers visiting the clinic for other purposes. The number of cases and controls was 87 people each and were matched by gender and citizenship. Data collected were age, travel plans, type of food and beverage consumption, hand washing habits and type of food providers (roadside food sellers, restaurants, hotel restaurants and food stalls). Multivariat analysis was performed using logistic regression to determine the adjusted odds ratio (AOR) of each risk factor. Results: Characteristics of cases and controls do not differ in terms of gender and citizenship. Multivariate analysis shows that significant risk factors associated with diarrhea in foreign travellers are a history of consuming street food with AOR=3.94 (95%CI: 1.19-12.97) and a history of traditional barbequed pork consumption (called babi guling) with AOR=6.24 (95%CI: 2.09-18.64). Other risk factors, namely consumptions of Indonesian food, traditional mixed chopped meat and vegetables (called lawar), mixed rice and drinks with ice cubes, are not found to be associated with the incidence of diarrhea in foreign travellers. Conclusion: Consumptions of street food and traditional barbequed pork were found to be associated with the incidence of diarrhea in foreign travellers during a visit to Bali. Street food hygiene, education for food vendors and information provision to foreign travellers on choosing food types need to be improved